Un approccio sperimentale allo spin elettronico - Fetto, Pasquale; Soldà, Roberto (Chimica nella Scuola, 2022)
It is known that the concept of electron spin, like that of orbital, should be introduced by using quantum mechanics. Therefore, this concept can be proposed in a fairly rigorous way only for the three years of high school with a chemical orientation, in which until 2010 was included, among other chemistry teachings, also physical chemistry that enabled to adequately treat elements of quantum mechanics. Currently, in the three years at a vocational level of chemistry, physical chemistry is integrated into the three disciplinary fields attributable to the teachings of chemical analytics, organic chemistry, and industrial chemical technologies. Therefore, these elements of quantum mechanics are introduced only within the limits of the possibilities and unfortunately in a theoretical-descriptive way, even if an experimental approach would be appropriate. Despite the difficulty, this article proposes an “approach” to the concept of electronic spin, as was done years ago in this same magazine for the concept of orbital.